IDENTIFIKASI FAKTOR RESIKO KEJADIAN INFEKSI NOSOKOMIAL PNEUMONIA PADA PASIEN YANG TERPASANG VENTILATOR DI RUANG INTENSIVE CARE - EKA ' SUASANTI; Wasisto ' Utomo; Yulia Irvani Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract The purpose of this reserach was to identify risk factors of nosocomial pneumonia infection incidence in patients with ventilator installed in the Intensive Care. This study used a descriptive retrospective method. This research was conducted in the Intensive Care of Islam Ibu Sina Hospital with 30 patients .The analysis used univariate analysis. The results show the frequency distribution of respondents who installed the ventilator based on the age of majority aged 18-60 years were 19 respondents (63.3%), the majority of respondents male sex as much as 17 respondents (56.7%), respondents who use sedation as much as 20 respondents (66.7%), respondents with albumin levels over 2.2 mg / dl were 24 respondents (80%), respondents with this type of disease is not lung disease as much as 21 respondents (70%) and respondents with no VAP by 22 respondents (70%). The results of this research recommends to health institutions to perform measurements on VAP assessment. Keywords:  Mechanical Ventilation, VAP